Internet Of Things (Iot) Based Water Quality Monitoring And Control System in Koi Fish Cultivation with Mobile Application Integration Named Aquakoi - Yanis, Naili Ikrimah M.; Munadi, Rendy; Fitriyanti, Nurwulan (eProceedings of Engineering, 2024)
William, I. Ruslianto, and I. Nirmala,